A phenomenological approach to psychological treatment for the multidisciplinary care of chronic back pain - F, Cecchi (International Journal of Psychosocial Rehabilitation, 2013)
psycho-social model and to recent theories of emotions. This paper aims at providing a systematic description of a psychological inter- vention based on a phenomenological approach within the multidisciplinary treatment of CBP. Methods. Starting form the theory of disfunction in CBP and the theory of treatment, we describe here the theoretical framework and process components of a short-term, emotionally focused psychological intervention, to explain the choice we made to use a phenomen- ological approach to illness and pain, in terms of group context into the patients’ rehabilitation care pathway. Conclusions. A phenomenological approach within the multidisciplinary treatment of CBP aims at the recognition of the subjective ex- perience of illness, emotions associated to the illness and individual ways to communicate pain, with the ultimate intended outcome of relieving pain-related psychological distress and improving pain management. A systematic description of this approach may facilitate its integration in clinical practice.